Nurse managers on healthy environments for adolescents living with intellectual disabilities - Rakgadi G. Malapela (AOSIS, 2024)
Background: Providing care for adolescents living with intellectual disabilities (ALWIDs) within healthcare settings is a complex challenge. These adolescents require an environment that is specialised and conducive to their health, alongside tailored care, treatment and rehabilitation services. Nurse managers play a crucial role in supporting these adolescents, particularly given the difficulties parents face in meeting their unique needs. Objectives: This study aims to explore nurse managers' perspectives on the creation of a healthy environment for ALWIDs in health facilities. Method: An explorative qualitative study design was conducted. A purposive sampling method was used to select 13 nurse managers from three institutions relevant to the study's interests. Nurse managers with over 2 years of direct experience in the care, treatment and rehabilitation of ALWIDs were eligible to participate in the study. Selecting these nurse managers ensured the study captured their firsthand experiences and expertise in managing nursing services. Data were collected through face-to-face and telephonic semi-structured interviews, recorded digitally. Braun and Clarke's six-step thematic analysis was used for data analysis. Results: A safe environment; multi-disciplinary team involvement; competent and adequate staff and a conducive physical environment for structural support are beneficial for ALWIDs. Conclusion: To promote the well-being of ALWIDs, it is essential to establish a spacious and safe environment equipped with sufficient material and non-material resources. Engaging a multi-disciplinary team is vital for addressing their diverse needs. Contribution: This study provided information on what constitutes a healthy environment for ALWIDs to inform clinical practice, nursing education, policy makers and research.